Near-infrared organic photodetectors based on bay-annulated indigo showing broadband absorption and high detectivities up to 1.1 μm. Issue 43 (22nd October 2018) - Verstraeten, Frederik; Gielen, Sam; Verstappen, Pieter; Kesters, Jurgen; Georgitzikis, Epimitheas; Raymakers, Jorne; Cheyns, David; Malinowski, Pawel; Daenen, Michaël; Lutsen, Laurence; Vandewal, Koen; Maes, Wouter
Abstract : Organic photodetectors made from a BAI-based near-infrared copolymer reach high detectivities of 10 12 Jones and low dark currents of 10 −7 A cm −2 . Abstract : Near-infrared photodetection is valuable for numerous scientific, industrial and recreational applications. The implementation of organic semiconductors in near-infrared photodetectors offers additional advantages, such as printability on flexible substrates, reduced manufacturing costs and facile tuning of the detection range. In this work, the nature-inspired bay-annulated indigo (BAI) dye is employed as a building block for near-infrared sensitive, push–pull type conjugated polymers. The electron-deficient BAI moiety is copolymerized with a set of electron-rich monomers, affording polymers with an absorption onset up to 1300 nm and a sufficiently high lowest unoccupied molecular orbital, allowing electron transfer to standard fullerene acceptors. Bulk heterojunction type organic photodetectors are fabricated and the resulting device characteristics are analysed. The best performing photodetector is based on the polymerPTTBAI comprising thieno[3, 2- b ]thiophene as the electron-rich moiety. It has a superior light to dark current ratio, with a dark current density of 10 −7 A cm −2, resulting in a (shot-noise limited) detectivity of 10 12 Jones at −2 V bias within the spectral window of 600–1100 nm, exceeding the detectivity of conventional silicon CCD photodetectors in the near-infrared region (∼10 11 Jones).